Open House. - Roussel, Noëllie; Walentiny, Christine; Alvim, Fernando; Jancekova, Viera; Faber, Laure; Munder, Heike; Budak, Adam; Gonzalez-Sancho, Eva; Hlavajova, Maria; Heldenstein, Bettina; Pinto, Roberto; Jouanno, Evelyne; et al. (Luxembourg : Casino Luxembourg - Forum d'Art Contemporain Luxembourg, 2002)
Alexander, Andy ; Biehler, Christine ; Bouchet, Gast ; Cierna, Pavlina Fichta ; Gillen, Tina ; Jahnke, Katharina ; Lawler, Louise ; Lopéz-Menchero, Emilio ; Recarens, Tere ; O'Malley, Niamh ; Rajkowska, Joanna ; Umbaca, Enzo ; Xhafa, Sislej
Casino Luxembourg - Forum d'art contemporain, Luxembourg, 22.06 - 15.09.2002
kunstcatalogus